2016
DOI: 10.1016/j.memsci.2015.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Pure- and mixed-gas permeation properties of highly selective and plasticization resistant hydroxyl-diamine-based 6FDA polyimides for CO2/CH4 separation

Abstract: The effect of hydroxyl functionalization on the m-phenylene diamine moiety of 6FDA dianhydride-based polyimides was investigated for gas separation applications. Pure-gas permeability coefficients of He, H 2 , N 2 , O 2 , CH 4 , and CO 2 were measured at 35 °C and 2 atm.The introduction of hydroxyl groups in the diamine moiety of 6FDA-diaminophenol (DAP) and 6FDA-diamino resorcinol (DAR) polyimides tightened the overall polymer structure due to increased charge transfer complex formation compared to unfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 48 publications
11
75
0
Order By: Relevance
“…The solubility coefficient of carbon dioxide in dihydroxylfunctionalized TPDA-DAR was 12% higher than that of TPDA-mPDA. This finding is in agreement with previous work, which showed that the introduction of hydroxyl groups into 6FDA-based polyimide membranes increased the solubility of CO 2 [42,53]. More importantly, however, is the decrease in diffusion coefficients and increase in diffusion selectivity in the TPDA-DAR polyimide due to hydroxyl functionalization; for example, the CO 2 diffusion coefficient decreased by 45% from 6.95 to 3.84 x 10 -8 cm 2 s -1 .…”
Section: A C C E P T E Dsupporting
confidence: 92%
See 2 more Smart Citations
“…The solubility coefficient of carbon dioxide in dihydroxylfunctionalized TPDA-DAR was 12% higher than that of TPDA-mPDA. This finding is in agreement with previous work, which showed that the introduction of hydroxyl groups into 6FDA-based polyimide membranes increased the solubility of CO 2 [42,53]. More importantly, however, is the decrease in diffusion coefficients and increase in diffusion selectivity in the TPDA-DAR polyimide due to hydroxyl functionalization; for example, the CO 2 diffusion coefficient decreased by 45% from 6.95 to 3.84 x 10 -8 cm 2 s -1 .…”
Section: A C C E P T E Dsupporting
confidence: 92%
“…ACCEPTED MANUSCRIPT [42,58]. As expected, the increase in selectivity was coupled with a 38% decrease in CO 2 permeability from 349 barrers to 215 barrers.…”
Section: A C C E P T E Dsupporting
confidence: 67%
See 1 more Smart Citation
“…Unfortunately, differently from what observed for the latter materials, MFC-Lup membranes show a selectivity that decreases when the RH exceeds 50 %, leading to a worsening of the general separation performance. This fact seems once again related to the effect of water on the materials transport properties: plasticization and swelling, are indeed known to decrease membrane selectivity as they increases to a bigger extent the diffusion coefficient of the gases with larger kinetic diameters[58][59][60][61]. The CO 2 /N 2 or CO 2 /CH 4 separation factor of many glassy polymers, for example, is reported to be negatively affected by the presence of CO 2 concentrations able to swell the membrane matrix[23,60,61], so that ideal selectivity results are much higher than the one measured under real conditions, when both the gaseous penetrants are present within the membrane matrix.…”
mentioning
confidence: 99%
“…This fact seems once again related to the effect of water on the materials transport properties: plasticization and swelling, are indeed known to decrease membrane selectivity as they increases to a bigger extent the diffusion coefficient of the gases with larger kinetic diameters[58][59][60][61]. The CO 2 /N 2 or CO 2 /CH 4 separation factor of many glassy polymers, for example, is reported to be negatively affected by the presence of CO 2 concentrations able to swell the membrane matrix[23,60,61], so that ideal selectivity results are much higher than the one measured under real conditions, when both the gaseous penetrants are present within the membrane matrix. It should be noticed however that, in the present case, water plasticization effects, are far more important than that induced by the incondensable penetrants, so that present ideal selectivity values should remain almost unchanged also in case of mixed gas experiments performed at similar RH.Figure 10.…”
mentioning
confidence: 99%